FROM PASSWORDS TO PERCEPTIONS: A COMPREHENSIVE ANALYSIS OF ONLINE BANKING SECURITY AND CUSTOMER BEHAVIOR - Dutta, Gaurav; Khurana, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This comprehensive research paper examines the intricate relationship between cyber security measures and customer behaviour in the context of online banking. As digital banking services have experienced exponential growth in recent years, financial institutions face the dual challenge of ensuring robust security protocols while maintaining customer trust and ease of use. This study surveyed a diverse group of 500 online banking customers in the National Capital Region of India to assess how various security protocols, awareness initiatives, and incident response capabilities influence customer perceptions and willingness to utilize online banking platforms. The findings indicate that while strong security measures are essential for customer confidence, overly rigid or complex protocols can negatively impact the user experience and potentially deter adoption. Specifically, 82 out of 100 respondents agreed that online banking improves efficiency, but 58 out of 100 expressed concerns about potential information leaks. Additionally, 71 out of 100 users viewed regular security updates and customer awareness programs positively, highlighting the importance of on-going communication and education.